Six simple twists : the pleat pattern approach to origami tessellation design - DiLeonardo-Parker, Benjamin (Boca Raton, FL : A K Peters/CRC Press, 2021)
This new edition of Six Simple Twists: The Pleat Pattern Approach to Origami Tessellation Design introduces an innovative pleat pattern technique for origami designs that is easily accessible to anyone who enjoys the geometry of paper. The book begins with six basic forms meant to ease the reader into the style, and then systematically scaffolds the instructions to build a strong understanding of the techniques, leading to instructions on a limitless number of patterns. It then describes a process of designing additional building blocks. At the end, what emerges is a fascinating artform that will enrich folders for many years. Unlike standard, project-based origami books, Six Simple Twists focuses on how to design, rather than construct. In this thoroughly updated second edition, the book explores new techniques and example tessellations, with full-page images, and mathematical analysis of the patterns. A reader will, through practice, gain the ability to create still more complex and fascinating designs. Key Features Introduces the reader to origami tessellations and demonstrates their place in the origami community New layout and instructional approach restructure the book from the ground up Addresses common tessellation questions, such as what types of paper are best to use, and how this artform rose in popularity Teaches the reader how to grid a sheet of paper and the importance of the pre-creases Gives the reader the ability to create and understand tessellations through scaffolded instruction Includes exercises to test understanding Introduces a new notation system for precisely describing pleat intersections Analyzes pleat intersections mathematically using geometrically-focused models, including information about Brocard points
Part I1.00 - Why Study Pleat Patterns?1.01 - Basics and Preparation1.02 - How Pleat Patterns Differ from Traditional Origami1.03 - How to Read the Diagrams and Fold Parity1.04 - Folding Uniform Parallel Creases1.05 - Grid Axes and How to Fold a Hexagon1.06 - How to Fold a Triangle Grid1.07 - Simple Pleat1.08 - The Six Simple Twists1.09 - Triangle Twist1.10 - Triangle Spread1.11 - Hex Twist1.12 - Hex Spread1.13 - Rhombic Twist1.14 - Arrow Twist1.15 - Anatomy of a Molecule1.16 - Pleat Intersection NotationPart II2.00 - How to Use the Six Simple Twists2.01 - 32nd's Grid2.02 - Locking and Unlocking Pleats2.03 - Triangle Twist Tessellation2.04 - 3.6.3.6 Tessellation2.05 - Tessellation Basics2.06 - Applying Tessellation Knowledge Folding2.07 - Triangle Weave Tessellation2.08 - 3.6.3.6 Weave Tessellation2.09 - 6.6.6 Hexagonal Failing Cluster2.10 - Modifications2.11 - Backtwisting2.12 - Twist Handedness and Pleat Symmetry2.13 - Pleat Flattening2.14 - Triangle Twist Tessellation with Flattened Pleats2.15 - Hidden Circles Pattern2.16 - Rhombic Twist Tessellation2.17 - Rhombic Twist Variants2.18 - Twist Sinking2.19 - Twist Expansion2.20 - Nub Offset Tessellation2.21 - Shift Rosette Tessellation2.22 - Ridge Creation2.23 - Button Molecule 2.24 - Button Molecule Tessellation2.25 - Triangle Flagstone Tessellation and Offsetting Pleats2.26 - 3.6.3.6 Flagstone Tessellation2.27 - Crooked Split2.28 - Snowflake Tessellation2.29 - Tulip Split2.30 - Tulip Split Tessellation2.31 - Molecule Size and Different Grid Densities2.32 - "Front" and "Back" Sides2.33 - Tendril Tessellation2.34 - Inverting a Pleat2.35 - Iso-Area Triangle Twist Tessellation2.36. - Pleat Pushing2.37 - Platform Tess2.38 - Triple Twist TessPart III3.00 - Pleat Patterns as Artwork3.01 - Gallery3.02 - Pleat-to-Molecule Analysis3.03 - Twist Archetype Sets3.04 - Molecule Database3.05 - Archetype Composition3.06 - Actions and Notation3.07 - Splitting Equation3.08 - Normal Polygon Models3.09 - Circle Cutout Model3.10 - Molecule-to-Pleat Analysis3.11 - Sectioning Model of Perfect Twist Design3.12 - Brocard PointsFinal thoughtsPleat Notation Thoughts By Matthew BenetGlossary
OCLC-licensed vendor bibliographic record.
Keywords: Paper work; MATHEMATICS / General; MATHEMATICS / Geometry / General; MATHEMATICS / Recreations & Games